VIRTUAL REALITY: evolution and future of gaming - Calderone, Washington Miscossi; Pinto, Giuliano Scombatti (Revista Interface Tecnológica, 2024)
This article explores the development and future of virtual reality (VR) gaming, highlighting its technological innovations, the impact on the gaming industry, and the challenges faced. The research was conducted through a quantitative approach using secondary data from academic articles and technical reports. The analysis focuses on technological advancements, such as high-quality graphics and motion sensors, which enhance immersion. The results highlight challenges such as the high cost of devices and cyber sickness, as well as promising future opportunities with the integration into the metaverse and the use of artificial intelligence (AI). The conclusion points out that, despite obstacles, VR has the potential to transform gaming and other sectors, such as education and healthcare, provided that devices become more affordable and technologies continue to evolve.
Keywords: Virtual Reality; Electronic Games; Technological Innovation; Immersion; Future Trends